Conservative Management of Dens Invaginatus Type IIIb Using Photodynamic Therapy: A Case Report - Nasrabadi , Navid; Yazdani, Atoosa; Mehrabani, Mahgol (Iranian Endodontic Journal, 2024)
Dens invagination (DI) is a developmental dental anomaly characterized by the infolding of the enamel organ into the dental papilla. Type IIIb DI, involving deep invagination that extends apically along the root, poses significant challenges in endodontic treatment due to its complex anatomy. We describe a case of type IIIb DI in a 13-year-old female referred with the chief complaint of spontaneous pain on the left maxillary lateral incisor. Clinical examinations showed tenderness to percussion and palpation as well as a positive response to cold test with lingering pain. Cone-beam computed tomography (CBCT) confirmed the presence of type IIIb DI associated with a periapical lesion. The final diagnosis was irreversible pulpitis with apical periodontitis for main canal (distal) and pulpless and infected root canal system with secondary acute apical periodontitis according to Abbott classification for the other canal. Two separate access cavities were prepared with the guidance of CBCT. Root canal therapy was performed on both root canals, using photodynamic therapy (PDT) and ultrasonic-activated sodium hypochlorite for enhanced disinfection. Calcium-enriched mixture cement was used to obturate the apical third, followed by thermoplastic gutta-percha in the middle and coronal thirds. The patient was asymptomatic at 6- and 12-month follow-ups, with radiographic evidence of complete healing. This case highlights the effectiveness of conservative endodontic treatment using PTD in managing complex DI cases, with a focus on maintaining tooth structure and achieving long-term success.